954 Sarcoidosis Mimicking Progression of Melanoma: A Case Report. (19th August 2022) - Quigley, A; Al-Khattab, M; Kennedy, S; Kelly, J
Abstract: A 78-year-old lady with a history of malignant melanoma on the dorsal aspect of her left foot, presented with a new fluorodeoxyglucose positron emission tomography (FDG-PET) avid lesion in her left fibular head. The patient had been diagnosed eight months previously with a 5.1mm Breslow thickness invasive melanoma. Following initial diagnosis, she underwent a wide local excision and sentinel lymph node biopsy (SLN). The melanoma was completely excised and SLN was negative for malignancy. Postoperatively, she underwent radiological staging with computed tomography scans (CT) of her thorax, abdomen, and pelvis. This showed scattered pulmonary nodules, and multiple indeterminate liver lesions. A PET scan was then performed, which showed an expansile, FDG-avid, lytic lesion in the left fibular head, suspicious for bone metastasis. Following discussion at the multidisciplinary team meeting, the patient underwent an open biopsy of the fibular head. Histology revealed non-necrotising epitheloid granulomata without evidence of malignancy. Ziehl-Neelsen and periodic acid Schiff stains were negative. The findings were suggestive of sarcoidosis. The patient revealed she had a previous diagnosis of pulmonary sarcoidosis 25 years prior, however, had no known extrapulmonary disease and was not attending a specialist. The pulmonary findings on CT were consistent with sarcoidosis. Sarcoidosis is a systemic inflammatory disease characterised by the development of non-caseating granulomata which typically affect the lungs and lymph nodes but can affect multiple organ systems. This case highlights the diagnostic uncertainty of an FDG-avid lesion on PET, necessitating diagnostic biopsy. Sarcoidosis is an uncommon but possible differential in this setting.